CHEMICAL COMPOSITION, ANTIOXIDANT ACTIVITY, AND FATTY ACID PROFILE OF COCOA NIBS - Penido, Fernanda Côrrea Leal; Lourenço, Isabelle Cristine Ramos; Silva, Lívia Mariana da; Garcia, Cleverson Fernando; Rezende, Flávia Augusta Guilherme Gonçalves (International Journal of Research -GRANTHAALAYAH, 2021)
Cocoa nibs ( cacao L.) are the cocoa beans after being fermented, dried, broken into small pieces, and then toasted. The cocoa nib composition is primordial for producers, industry, and final consumers because it affects the final quality of the raw material and any derivative product. The chemical composition was analyzed using , , , and Scharrer-Kurschner methods. The results showed that the cocoa nibs studied were rich in lipids (44.02 ± 5.22%), followed by carbohydrates (25.30%), raw fiber (12.85 ± 3.67%), protein (10.73 ± 1.80%), and ash content (2.58 ± 0.15%). The fatty acid profile was determined by gas chromatography and showed the presence of , , and acids. The low moisture content (4.52 ± 0.12%) and total acidity (2.25 ± 0.45 NaOH 100 g-1) contributed to the low count of microorganisms, which may give cocoa nibs a longer shelf life. Additionally, it presented high antioxidant activity, with a total content of 843.45 ± 11.85 mg acid / 100 g extract and 89.42 ± 0.02% iron reducing power.